Implementasi Emotional Spiritual Quotient (ESQ) dalam Keteladanan Kepemimpinan Jawa di Madrasah - Umi Arifah; Sulis Rokhmawanto; Rahmawati Rahmawati (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2022)
The purpose of this study was to analyze the implementation of Emotional Spiritual Quotient (ESQ) in exemplary Javanese leadership at Madrasah Aliyah GUPPI, Rakit District, Banjarnegara Regency. The research was conducted with a qualitative approach and data collection was carried out by observation, interviews, and documentation. The results of the research on Javanese leadership of Madrasah Heads were carried out by giving examples in behavior and work and being polite in speaking. The leadership of the madrasa head not only gives orders, but also shows an exemplary attitude in all aspects, both discipline, responsibility, cleanliness and so on.